2014
DOI: 10.1515/ract-2014-2120
|View full text |Cite
|
Sign up to set email alerts
|

An advanced purex process based on salt-free reductants

Abstract: An advanced plutonium and uranium recovery process has been established based on two organic reductants, , -dimethylhydroxylamine (DMHAN) and methylhydrazine (MH), as U/Pu separation reagents. This Advanced Purex process based on Organic Reductants (APOR) is composed of three cycles, including U/Pu codecontamination/separation cycle, uranium purification cycle and plutonium purification cycle. Using DMHAN and MH as plutonium stripping reagents in the U/Pu codecontamination/separation cycle and plutonium purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…More importantly, its isotope ( 237 Np) is the raw material for 238 Pu, which can be used to prepare nuclear power batteries . For Advanced PUREX (Plutonium Uranium Reduction EXtraction) and SUPERPUREX, the Np separation can be achieved in the PUREX process according to the extraction difference of tributyl phosphate (TBP) for three oxidation states (Np­(VI) > Np­(IV) ≫ Np­(V)). Some highly efficient and green free-salt reductants have been studied to reduce Np­(VI) in the experiment such as aldehydes, hydroxylamine, oximes, , hydrazine, and their derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, its isotope ( 237 Np) is the raw material for 238 Pu, which can be used to prepare nuclear power batteries . For Advanced PUREX (Plutonium Uranium Reduction EXtraction) and SUPERPUREX, the Np separation can be achieved in the PUREX process according to the extraction difference of tributyl phosphate (TBP) for three oxidation states (Np­(VI) > Np­(IV) ≫ Np­(V)). Some highly efficient and green free-salt reductants have been studied to reduce Np­(VI) in the experiment such as aldehydes, hydroxylamine, oximes, , hydrazine, and their derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…The studies on the reduction of Pu­(IV) have been explored in experiments using various reductants, including the combination of U­(IV) with hydrazine and salt-free reductants such as formo- and acetohydroxamic acid, tert -butyl hydroquinone, aldehydes, , hydroxylamines, hydroxyurea, hydrazine, oximes, and their derivatives. Of these, oxime derivatives reduce Pu­(IV) to Pu­(III) in HNO 3 solution with excellent stability, fast nitrous acid scavenging, and kinetics. , ,− Koltunov et al first reported the reduction of Pu­(IV) by acetaldoxime in nitric acid and obtained the activation energy with the value of 87.7 ± 9.8 kJ mol –1 at 298 K .…”
Section: Introductionmentioning
confidence: 99%